English Teachers’ Experiences in Online Learning During The Covid-19 Pandemic at State Elementary School 005 Samarinda - Simbolon Selfania Mastauli; Ventje Jany Kalukar; Weningtyas Parama Iswari (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
The COVID-19 pandemic forced a rapid transition from face-to-face instruction to online learning across all school levels in Indonesia. For instance, one teacher at State Elementary School 005 Samarinda managed daily English lessons via a WhatsApp group - sending voice notes to explain vocabulary, relaying assignments through parents for students without smartphones, and staying online until late evening to answer students' questions. This study examines how English teachers at this school adapted to emergency remote teaching, focusing on their challenges, coping strategies, and professional development outcomes. A qualitative phenomenological design was employed to capture teachers lived experiences. Semi structured interviews were conducted with three English teachers during the 2020/2021 academic year. Data were analyzed thematically to identify patterns of challenges, adaptation, and benefits Teachers reported significant obstacles, including limited digital literacy, unstable internet access, and reduced student engagement. Despite these barriers, the transition fostered professional development, particularly in digital competence and communication through platforms such as WhatsApp, Google Classroom, and Google Meet. The study concludes that while online learning disrupted established practices, it also acted as a catalyst for teacher resilience and technological growth. Continuous technical training and infrastructure support are recommended to strengthen preparedness for future blended learning environments. Previous studies have examined online learning broadly, but few focus on elementary English teachers in Samarinda. This research fills that gap by documenting localized experiences, offering insights into resilience and adaptation in resource‑limited contexts